Weekly Averaged Blood Pressure Is More Important than a Single-Point Blood Pressure Measurement in the Risk Stratification of Dialysis Patients - Moriya, Hidekazu (American Society of Nephrology, 2008)
Background and objectives: With regard to monitoring blood pressure in hemodialysis patients, it is important to define clearly the time point at which the blood pressure is measured, because the blood pressure of hemodialysis patients varies with each hemodialysis session as a result of loss of excess fluid. Design, setting, participants, & measurements: Using weekly averaged blood pressure, 96 hemodialysis patients were studied prospectively for 35 mo. All patients were followed up for cardiovascular events or death from all causes. Results: Pulse weekly averaged blood pressure and age at enrollment were significantly higher and parathyroid hormone level was significantly lower in patients with cardiovascular events compared with those without cardiovascular events; however, none of the components of pre- or postdialysis blood pressure was significantly different between patients with and without cardiovascular events. Pulse weekly averaged blood pressure, prepulse pressure, age, and human atrial natriuretic peptide were significantly higher in patients who died than in survivors. Kaplan-Meier method with a log-rank test demonstrated that survival free rate from cardiovascular events and that of all-cause mortality in patients with pulse weekly averaged blood pressure ≥70 mmHg were significantly lower than those in the remaining patients. Conclusions: One-point measurement of blood pressure is insufficient to evaluate hypertension and prognosis of hemodialysis patients, and weekly averaged blood pressure is a useful marker because of averaging fluctuations of blood pressure during 1 wk. Among components of weekly averaged blood pressure, pulse weekly averaged blood pressure could be a good prognostic marker of the incidence of both cardiovascular events and all-cause mortality in hemodialysis patients.